1998
DOI: 10.1074/jbc.273.26.15895
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Domain of HIV Tat Involved in Monocyte Chemotaxis

Abstract: Human immunodeficiency virus (HIV)Tat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 40 publications
5
90
0
2
Order By: Relevance
“…This study monitored the intracellular calcium flux for 30 min using microspectrofluorimetry with images captured every 5 s, while our study observed the intracellular calcium flux over 3 min using real time flow cytometry. Using this method, we detected a rapid and transient calcium flux following B Tat treatment that is consistent with other studies using similar methods (5,9,30,48) that was possibly missed using a time-lapse method. Our results also show that Ca L and PI3K inhibitors reduce the ability of clade B Tat to induce IL-10 production in monocytes.…”
Section: Discussionsupporting
confidence: 77%
“…This study monitored the intracellular calcium flux for 30 min using microspectrofluorimetry with images captured every 5 s, while our study observed the intracellular calcium flux over 3 min using real time flow cytometry. Using this method, we detected a rapid and transient calcium flux following B Tat treatment that is consistent with other studies using similar methods (5,9,30,48) that was possibly missed using a time-lapse method. Our results also show that Ca L and PI3K inhibitors reduce the ability of clade B Tat to induce IL-10 production in monocytes.…”
Section: Discussionsupporting
confidence: 77%
“…Cell migration assays were conducted on SH-SY5Y, ACN, and LA1-5S cells in microchambers (NeuroProbes Gaithersburg) as previously described (20). Cells were extensively washed with PBS, resuspended in serum-free medium, and placed in the upper compartment.…”
Section: Neuroblastoma Cell Migration Assaymentioning
confidence: 99%
“…In fact, a preponderance of reports has unequivocally established that Tat possesses a unique biological activity that alters the function of monocytes, dendritic cells (DCs), and CD4 ϩ and CD8 ϩ T cells in vitro (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In addition, detectable levels of extracellular Tat are found in culture supernatants from cells infected with HIV-1 (20)(21)(22), and Tat is efficiently taken up by a variety of cells (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%